Short ACTH test in assessing hypothalamic-pituitary-adrenocortical function. Issue 6004 (31st January 1976) - Kehlet, H; Blichert-Toft, M; Lindholm, J; Rasmussen, P
Abstract : The adrenocortical response to the simple 30-minute ACTH stimulation test was compared with the hypothalamic-pituitary-adrenocortical (HPA) response to insulin-induced hypoglycaemia in 25 patients with various degrees of hypothalamic-pituitary malfunction. The correlations between the increase in plasma cortisol during insulin hypoglycaemia and that during ACTH stimulation (r = 0-66) and between peak plasma cortisol levels during the two tests (r = 0-90) were highly significant. Peak plasma cortisol levels in individual patients were similar on both tests, no patient showing any major discrepancy between the two test results. Thus the simple 30-minute ACTH stimulation test seems to be reliable in detecting imparied HPA function.